Study of short-term dialysis via guanidino complex variations with time - Fujishiro, Toshitaka; Hasegawa, Hiroshi; Kojima, Kuniyoshi; Kawashima, Shiro; Ogawa, Tadashi; Yanai, Toshiyuki; Ikegame, Mamoru; Miura, Nobuhiko; Mitobe, Kyoko; Mizuno, Masao (Journal of Japanese Society for Dialysis Therapy, 1987)
Twenty-one dialysis patients were subjected to serum biochemical studies in which guanidino complex variations were observed in order to determine whether or not they would be helpful in determining the advisability of short-term dialysis. The results of these investigations were as follows 1) In serum biochemical studies, significant differences were observed between the four-hour and five-hour dialysis values for BUN, creatinine and UA (p<0.05), but no significant differences were noted between the 4.5- and five-hour values; 2) dialysis time was reduced by 30min per week and the categorized data totals for an approximate three-month period indicated a significant increase in predialysis serum creatinine values in five of six patients (p<0.005) and also a significant increase in BUN in two patients; 3) guanidino succinic acid and methylguanidine values in both serum and whole blood showed a tendency to be lower in the five-hour period in comparison with values for the four-hour period, but the differences were not significant; 4) methylguanidine was approximately doubled by a creatinine peroral load. Thereafter, there were no significant differences between the values obtained in the four-hour and five hour dialysis procedures, although even the values for the five-hour period were approximately double those for non-loading. Dialytic efficiency was lowered to a greater extent than creatinine levels. According to the possibility observed that methyl-guanidine accumulasion occurs in short-term dialysis performed by conventional dialysis methods, the above data indicate that long-term observation is necessary. If methylguanidine toxicity is regarded to be important, then shortening of the dialysis process by blood purification methods such as protein-permeable HDF in advisable.